Soft Skills Nurturing Altruistic Leaders - Rohana, Hamzah; Anita, Abdul Rani; Fatmawati, Latada; Haslinda, Hashim; Rashidi, Abbas; Mahyuddin, Ismail; Mohd Suhardi, Mat Jusoh; Norizan, Yusof (Centre for Human Sciences, UMP, 2022)
Alhamdulillah, finally, our dream of publishing an e-book, Soft Skills (1st Series), has turned into reality. The publication of this book is more meaningful as it is the first publication by the Centre of Human Sciences, UMP. This book is written especially for UMP students. Soft skills has become one of the university’s compulsory subjects in an effort to nurture holistic students who are not only excellence in knowledge and skills but also possess good personalities. Therefore, the topics discussed in this book are Spiritual Intelligence, Emotional Intelligence, Manners and Positive Values as a Leader in terms of Communication and Attitude in daily life and at work place.